How Do Faculty Members See the Curriculum Leadership Role in Post Graduate? A Qualitative Research - Maryam Avizhgan; Ebrahim Mirshah Jafari; Ahmad Reza Nasr; Tahereh Changiz (Kerman University of Medical Sciences, 2014)
Background & Objective: Leadership talent is the rarest resource in todays world that will have continuous conductivity the organizations to be successful in tomorrows world Considering the importance of curriculum leadership in educational department this study was designed to answer the question how do faculty members see curriculum leadership in the post graduate?   Methods: In a qualitative study with purposive sampling of desirable cases type faculty members with management experience and expert in the post graduate were selected and interviewed using semistructured method Data were analyzed using thematic content analysis including: data collection data reduction deduction and analysis in the MAXQDA software version 2007   Results: After interviewing 18 faculty members with sufficient experience and management experience in the postgraduate courses we achieved a richness of information saturation and data replicate 500 codes were extracted from research data under five main categories and were classified These categories included: educational atmosphere improvement curriculum development curriculum implementation curriculum evaluation and supervision innovation and facilitate change and adaptation   Conclusion: Participants in this study suggested five main categories and 18 subcategories that represented curriculum leadership roles These roles are in the applicable and comparable area with curriculum cycle including: the planning implementation supervision evaluation and change In addition these roles were also emphasized on educational atmosphere improvement that is platform background supplier infrastructure and prerequisites for the curriculum cycle